Analytical Study of Deaths Due to Suicidal Burns Based on Postmortem Examination - D , Laxmi; G Mahender; Shirisha, A; Kumar, B Ravi (Journal of Indian Academy of Forensic Medicine, 2024)
Heat is a form of energy which when transferred to the body causes thermal injury in the form of burns or scalds, the former due to dry heat and the latter due to moist heat. According to WHO, an estimated 1,80,000 deaths every year are caused by burns, the vast majority occur in low/middle-income countries and almost two-thirds occur in African and South-East Asia regions. According to World Health Statistics 2019, India's suicide rate stood at 17.8 suicides per 1,00,000 people, much higher than the global suicide rate of 10.5. The present study focuses on suicidal deaths due to burns to know the magnitude of the problem in our society, to identify which group of society is more vulnerable to this method of suicide and to investigate the outcome of self-inflicted burns and what measures can be taken to reduce the count. An observational study of 100 postmortem cases conducted during a period of 18 months i.e. from January 2019 to June 2020 conducted in Gandhi Medical College/hospital mortuary, Secunderabad, Telangana. The main sources of data are inquest reports, first investigation reports, postmortem reports, hospital case sheets, and death summaries (in treated cases and hospital deaths). The present study concluded that maximum deaths due to suicidal burns occurred in the age group of 31-40 years (35%) associated with equal preponderance of male (50%) and female (50%) groups. Victims whose total body surface area involved was less survived better. By providing proper timely counseling to the vulnerable population, the rate of suicides can be curbed to some extent. Also creating public awareness about the adverse effects of chronic alcoholism, if not all, few social problems can be avoided. As the rural population's preponderance is more in deaths due to suicidal burns, most of them succumb by the time they reach the hospital or health care centers. The delay in hospitalization enhances the complications of burn injuries. Providing adequate health care facilities, counseling centers for the vulnerable section of population and expansion of tertiary medical care all over the country to treat burns victims could be a major step to prevent deaths due to suicidal burns.
Keywords: Suicide; Burns; Degree of burns; Socioeconomic status; Period of survival; Total body surface area; Self-immolation; Kerosene; Soot